Liver transplantation normalizes serum hepcidin level and cures iron metabolism alterations in HFE hemochromatosis. Issue 3 (27th January 2014) - Bardou‐Jacquet, Edouard; Philip, Julie; Lorho, Richard; Ropert, Martine; Latournerie, Marianne; Houssel‐Debry, Pauline; Guyader, Dominique; Loréal, Olivier; Boudjema, Karim; Brissot, Pierre
<x xml:space="preserve">Abstract</x> Defects in human hemochromatosis protein (HFE) cause iron overload due to reduced hepatic hepcidin secretion. Liver transplantation (LT) is a key treatment for potential complications from HFE‐related hereditary hemochromatosis (HH). This study evaluated hepcidin secretion and iron burden after LT to elucidate HH pathophysiology. Patients (n = 18) homozygous for the p.Cys282Tyr mutation in the HFE gene underwent LT between 1999 and 2008. Serum iron, serum hepcidin, and hepatic iron concentrations were determined before LT and at the end of follow‐up (median 57 months). Mortality and causes of death were determined. Survival was compared to that of the overall patient population that received LT. Before LT, serum hepcidin levels were low (0.54 ± 2.5 nmol/L; normal range: 4‐30 nmol/L). After LT, 11 patients had iron evaluations; none received iron depletion therapy; all had normal transferrin saturation. The mean serum ferritin was 185 (±99) μg/L. Magnetic resonance imaging showed that iron overload was absent in nine patients, mild in one patient with metabolic syndrome, and high (180 μmol/g) in one patient with hereditary spherocytosis discovered after LT. At the end of follow‐up, serum hepcidin was normal in 10 patients (11.12 ± 7.6 nmol/L; P < 0.05) and low in one patient with iron deficiency anemia. Survival was 83% and 67% at 1 and 5 years, respectively. Survival was similar for patients with HH and patients that received LT for other causes. Conclusion: In HH, LT normalized hepcidin secretion and prevented recurrence of hepatic iron overload. Survival was similar to that of patients who received LTs for other liver diseases. (Hepatology 2014;59:839–847)